HARMONIZATION OF PANCASILA VALUES AND SHARIA PRINCIPLES IN THE INDONESIAN BANKING SYSTEM - Hermansyah, Hermansyah (Journal Civics And Social Studies, 2024)
In the context of the rapid growth of Islamic banking in Indonesia, it is essential to understand how the values of Pancasila can be integrated into financial practices to enhance public trust and support sustainable development. The aim of this research is to explore and analyze the challenges and opportunities in harmonizing Pancasila values with Islamic principles within the Indonesian banking system. The research employs a qualitative approach using in-depth interviews and document analysis to gain comprehensive insights from various stakeholders in the banking sector. The results indicate that there are common values between Pancasila and Islamic principles; however, challenges include differing interpretations and uneven understanding among industry players. This research recommends the development of policies that support the synergy between these two values, as well as training for stakeholders to improve understanding and harmonious implementation in banking practices.